The Effect of Mental Imagery Exercises Using Aiding Apparatuses on Improving Attention in Young Boxers - Ali Yahya Azeez; Azeez Kareem Wannas; Samer Abdulhadi Ahmed (College of Physical Education and Sport Sciences, 2021)
The research aimed at designing an electronic apparatus for developing forms of attention in young boxers as well as designing exercises for this apparatus for developing types of attention. In addition to that, it aims at identifying the effects of these standardized exercises using the designed apparatus on the development of attention in young boxers. The researchers used the experimental method on young boxers aged (13 - 16) years from the national center for gifted in boxing/ ministry of youth and sports. The apparatus was designed for developing attention and it was applied along with the proposed mental imagery exercises to develop attention. The program lasted for (12) weeks with (3) training sessions per week. The researchers concluded that attention was developed in young boxers and mental imagery exercises are very important for developing performance.